Effect of nanotoxicity and enhancement in performance of polymer composites using nanofillers: A state‐of‐the‐art review. Issue 5 (15th February 2021) - Das, Partha Pratim; Chaudhary, Vijay; Ahmad, Furkan; Manral, Ankit
Abstract: Polymer composite materials are consistently being used in various industrial and domestic applications due to their lightweight, high‐specific strength, and low cost. In order to enhance various performance of polymer composites, a suitable nanofiller can be used. Polymer composites, which take advantage of natural fibers and nanofillers, synergistically, contribute to improved properties and environmental condition by making them suitable for various applications (aerospace, automobile industries, electronics, biomedical, etc.). The present study gives an insight of nanofiller‐based polymer composite and the challenges associated with processing methods. The use of nanofillers in polymer composites to enhance their mechanical properties (tensile, flexural, impact, and tribological) and most importantly the self‐healing property due to which they are finding numerous applications. This study also includes the problems associated with excessive use of nanomaterial leading to various environmental and health hazards. The problems and their remedies associated with nano‐toxicity have also been addressed. Abstract :